Benthic foraminifers in coastal habitats of Ras Mohamed Nature Reserve, southern Sinai, Red Sea, Egypt - A. M. BadrElDin; P. Hallock (Journal of Micropalaeontology, 2024)
The Red Sea is globally recognized for its exceptional diversity of marine environments despite relatively high salinities (39–41). Unfortunately, as elsewhere, anthropogenic activities are degrading coastal environments, including coral reefs. We examined foraminiferal distributions to assess the ecological status of coral reef environments in the coastal area of the Ras Mohamed Nature Reserve (RMNR) in the southern Sinai coastal region. Sediment samples were collected in mangrove, shallow-lagoon, nearshore, and coral reef habitats. Overall, 95 species were recorded. Five benthic foraminiferal species that host algal symbionts dominated the assemblages, representing ∼60 % of the assemblages, along with one porcelaneous heterotrophic species (Quinqueloculina seminulum; ∼8 %). The symbiont-bearing species were three porcelaneous forms (Amphisorus hemprichii, Peneroplis pertusus, and P. planatus) and two hyaline taxa (Amphistegina lobifera and A. lessonii). Peneroplis and Amphisorus dominated shallow-bay and mangrove channel assemblages, where carbonate sediments predominated, whereas Amphistegina were most abundant in reef sediments. The results of diversity and heterogeneity indices, including the Shannon–Wiener index (H′), the Simpson index (D), and the evenness index (E), were remarkably consistent. The foraminiferal assemblages are characterized by low diversity (H′), low evenness, and often high dominance (D). Values of the FoRAM Index consistently exceeded four, indicating water quality suitable for carbonate production and accretion. Relatively high percentages of foraminifers were collected live (stained), with up to 18 % of the total assemblage in some localities. The low α-Fisher indices and commonly observed “abnormal” peneroplid and soritid specimens reflect that these metrics must be used with caution when assessing tropical–subtropical shallow-water assemblages in hypersaline environments. Benthic species that host algal symbionts represent a tiny fraction of total numbers of benthic species, yet photosynthesis by the algal symbionts allows the dominance of those few in clear, shallow, reef-associated waters where particulate food is limited. In addition, morphological variability is extremely common in peneroplids and soritids for reasons not fully understood.